The Impact of The COVID-19 Pandemic on Indonesian Retail Companies' Working Capital Management - Setiawan, Wimpie Yustino; Hutomo, Yohanes Berchmans Sigit (KINERJA, 2023)
Indonesian government imposed a social distancing policy in response to the declaration of COVID-19 as a pandemic but still allowed companies to operate their business with several restrictions. As a result, retail companies had to manage their working capital more prudently in order to keep the stability of their business operations. This research aims to examine the impact of the COVID-19 pandemic on the working capital management of Indonesian retail companies listed on the Indonesia Stock Exchange. The results of the current study showed that the COVID-19 pandemic did not affect profitability (measured by return on assets and return on equity) and the working capital management (measured by cash conversion cycle and working capital requirement) of retail companies. However, other proxies of working capital management (i.e., net liquid balance and operating cash flow) were found to be significantly different before COVID-19 and during the pandemic.